1993
DOI: 10.1161/01.str.24.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social support on outcome in first stroke.

Abstract: Background and Purpose: The purpose of this study is to examine the impact of social support on outcome after first stroke in a prospective cohort study. Although modest evidence exists for the importance of several psychosocial factors, studies have failed to use widely recognized measures of outcome and social support, have failed to control for time since onset, and have not used longitudinal techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
207
4
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(224 citation statements)
references
References 22 publications
7
207
4
6
Order By: Relevance
“…Moreover, the majority of these studies (5)(6)(7)(8)10,11,16), in contrast with the present one, defined an initial short-term stage of around three months which is characterised by a relatively rapid recovery rate. Some of these studies (6,7) also report that 80-85% of the total recovery occurs during first month or month and a half, with 95% of the recovery having been achieved at three months.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Moreover, the majority of these studies (5)(6)(7)(8)10,11,16), in contrast with the present one, defined an initial short-term stage of around three months which is characterised by a relatively rapid recovery rate. Some of these studies (6,7) also report that 80-85% of the total recovery occurs during first month or month and a half, with 95% of the recovery having been achieved at three months.…”
Section: Resultscontrasting
confidence: 59%
“…Yet it has still been possible to discuss our results with reference to those elsewhere in the literature as the improvement percentages attributed to the different periods are also provided in terms of the commonly used assessment scales. Most of the studies cited use a scale for the assessment of the ADL -the Barthel index (4-7,11), -although some have employed motor indices such as the Functional Ambulation Category, Fugl-Meyer Assessment or the Motricity Index (5,9) or neurological scales such as the Scandinavian Stroke Scale (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that the use of assistive devices has a strong impact on stroke survivors' daily activities [7,8]. Another example is the widely accepted but less studied impact of social support, which facilitates stroke outcome [9,10]. The best documented environmental factor in the context of stroke is possibly stroke unit care as a type of health care service [11].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of social support a patient gets after having a stroke is positively associated with the extent of the functional status (Glass et al 1993) with socially isolated stroke patients being at risk of poor function (Glass et al 1993). Patients who have had a stroke generally function better in activities of daily living than they do in social activities and interactions (Schmidt et al 1986).…”
Section: Introductionmentioning
confidence: 99%